Use of eelgrass beds (Zostera marina) by juvenile Atlantic cod (Gadus morhua) - Gotceitas, Vytenis; Fraser, Sandra; Brown, Joseph A (Canadian Journal of Fisheries and Aquatic Sciences, 1997)
Two field surveys were conducted in Newfoundland, Canada: (1) SCUBA surveys at four sites differing in bottom type and the presence/absence of vegetation and (2) beach seining at three sites containing eelgrass (Zostera marina) and no-eelgrass locations. Results indicated that eelgrass is used as a nearshore habitat by age 0 + Atlantic cod (Gadus morhua). A subsequent laboratory experiment compared the use of patches of bottom substrates (sand, gravel, cobble) and artificial eelgrass (three densities) by age 0 + cod when in the absence and presence of a predator (an age 3 + conspecific). Before exposure to a predator, age 0 + cod associated with sand and gravel. With a predator present, in substrate combinations with cobble, age 0 + cod hid in the interstitial spaces of this substrate or in the patch of eelgrass when stem density was >=>720 stems/m 2 . In combinations with no cobble, age 0 + cod hid in the eelgrass regardless of stem density. Latency to capture an age 0 + cod was highest and the total number of age 0 + cod captured lowest in combinations with cobble or the patch of vegetation with 1000 stems/m 2 . In the remaining combinations, latency until an age 0 + cod was captured increased with both the presence and density of vegetation.